Le rôle de la banque d’Algérie dans la formalisation de la finance informelle The role of the Bank of Algeria in the formalization of informal finance - Nacéra DERDER; Abdelkader BENAMMAR (المجلة الدولية للأداء الاقتصادي, 2023)
This study aims to identify the extent of informal finance in Algeria, to review the main decisions taken by the central bank in its fight against the informal and discuss their impact on informal finance. Faced with an informal finance that persists, new actions must be taken, not only on the regulatory level, but must also be part of a strategy aimed at strengthening the operational efficiency of the banking system.